Penguatan konsep patung catur muka sebagai landmark Kota Denpasar - Putra, I Putu Rusdikananta; Asmiwyati, I Gusti Agung Ayu Rai; Astiningsih, Anak Agung Made (Jurnal Arsitektur Lansekap, 2019)
Strengthening the concept of the catur muka statue as the landmark of Denpasar. Denpasar is a city on the island of Bali and at once becomes the capital of the province of Bali, Indonesia and becomes economic growth centers in Bali. Such growth is supported by the existence of improvements in all sectors, including the landmark of Denpasar, The catur muka statue still can be strengthen by improving the internal and external quality. This study aims to explore the internal and external quality as well as the planned strengthening of the concept of the catur muka statue as the landmark of Denpasar. The research method used was survey method with techniques of observation, questionnaires, and supporting data through literature studies. Research results are processed by using the method of tabulate and descriptive analysis. The result of the analysis of the study showed the catur muka statue has all the internal and external quality required by a landmark, but not yet developed optimally. Strengthening planning concepts through design concepts, lighting and planting is required to improve the internal and external quality of the catur muka statue as a landmark of Denpasar.